Strategic Management of Sharia Hedging in Addressing Risks in the Digital Era - Hernawaty; Efrizal Adil; Patwa Nirmala (International Journal of Management, Economic and Accounting, 2025)
This study aims to explore the strategic management of sharia hedging in addressing risks in the digital era. With the rapid development of technology and digitalization, the Islamic financial sector is faced with new challenges, including market volatility, operational risk, and cyber threats. The methodology used in this study is qualitative analysis and case studies involving several Islamic financial institutions. The results show that the implementation of sharia-compliant sharia hedging strategies not only helps mitigate risks but also enhances institutional competitiveness in an ever-changing environment. The adopted strategies include the use of sharia-compliant instruments such as sukuk and derivative contracts, as well as digital innovation in risk management systems. This study recommends the importance of collaboration between regulators and practitioners to develop a more effective and sharia-compliant hedging framework, as well as the need for education for stakeholders in understanding and implementing hedging strategies in the digital era. These results are expected to make a significant contribution to the development of risk management practices in the Islamic financial industry.